THE USE OF DISCRIMINANT ANALYSIS IN THE FIELD OF SHIP NAVIGATION - Semenchuk, E. L. (Science and Transport Progress, 2009)
The technique of discriminant analysis on an example of the state Ukrainian shipping companies by dividing them on separate groups taking into account the strategic priorities is considered.